Integrating Pancasila Values in Islamic Education: A Learning Model Based on Azyumardi Azra’s Perspective - Deddy Yusuf Yudhyarta; Zamsiswaya Zamsiswaya; Asmal May (AL-ISHLAH: Jurnal Pendidikan, 2025)
Indonesia, as a Muslim-majority nation founded on Pancasila, faces ongoing challenges in harmonizing Islamic values with national ideology. Tensions between religious identity and nationalism, exemplified by increasing intolerance and declining civic awareness, highlight the urgent need for integrative educational approaches. This study explores Azyumardi Azra’s perspective on the alignment between Islam wasathiyyah (moderate Islam) and Pancasila, emphasizing Islamic education as a strategic medium to cultivate both religious and national character. This research adopts a qualitative method based on library research. Primary data sources include the works of Azyumardi Azra, scholarly articles, and official documents related to Pancasila and Islamic education. Data were analyzed descriptively and thematically to construct a conceptual model for integration. The findings reveal three main insights: (1) a value integration model that aligns Islamic principles—such as justice (‘adalah), brotherhood (ukhuwah), and deliberation (shura)—with the five principles of Pancasila; (2) the use of inclusive and contextual teaching methods to foster tolerance and civic responsibility; and (3) the importance of local cultural contexts in developing educational models that are both relevant and effective. This study contributes to the discourse on Islamic education by offering a theoretical framework for integrating religious and national values. By operationalizing Azra’s ideas into curriculum development and pedagogical practices, the research proposes a transformative model applicable in both formal and non-formal education. It underscores the potential of Islamic education to promote a tolerant, pluralist, and nationalist generation in contemporary Indonesia.